The Venona story - Benson, Robert Louis (Center for Cryptologic History, 2001)
Based on several public releases of VENONA translations and related documents, the study deals with revelations about Soviet atomic bomb espionage, KGB and GRU involvement in espionage against the U.S., and other topics.